Board Game sebagai Media Pendukung Murojaah Juz Amma untuk Anak Usia 6-8 Tahun - Safitri Nur Ramadhani; Masnuna Masnuna; Bayu Setiawan (Lembaga Pengembangan Kinerja Dosen, 2025)
The activity of murojaah or repeating the memorization of the Qur'an is an important part in the process of strengthening memory of the verses of the Qur'an that have been memorized. However, children often face challenges in maintaining the consistency of murojaah due to lack of motivation and lack of interesting learning methods. This design aims to explore the potential of board games as a supporting media for murojaah juz amma which is educational and fun. By having an attractive visual design, it is expected to be able to increase learning motivation, strengthen memory, and strengthen social interaction between players.